2020
DOI: 10.1155/2020/9082924
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Arm Port and Chest Port for Optimal Vascular Access Port in Patients with Breast Cancer: A Systematic Review and Meta-Analysis

Abstract: Objectives. This meta-analysis was conducted to compare the complication rates between arm and chest ports in patients with breast cancer. Design and Data Sources. PubMed, Embase, Cochrane library, Chinese National Knowledge Infrastructure (CNKI), and Wanfang database were used to perform a systematic review and meta-analysis of publications published from the inception of the database to 11, October 2019. Our search generated a total of 22 articles published from 2011 to 2019, including 6 comparative studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…With the increasing number of patients with cancer, physicians have shown interest in TIVAD insertion using a percutaneous approach (17). The selection of venous sites and approaches for TIVAD have already been discussed in literature (18)(19)(20)(21)(22). According to a 27-year comprehensive review of TIVAD insertion, a cut-down manoeuvre was not the predominantly used approach (42.8%) (18).…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing number of patients with cancer, physicians have shown interest in TIVAD insertion using a percutaneous approach (17). The selection of venous sites and approaches for TIVAD have already been discussed in literature (18)(19)(20)(21)(22). According to a 27-year comprehensive review of TIVAD insertion, a cut-down manoeuvre was not the predominantly used approach (42.8%) (18).…”
Section: Discussionmentioning
confidence: 99%
“…These indwelling vascular accesses enable the delivery of chemotherapeutic drugs or blood products and can be used for blood draws, avoiding the possible local complications associated with the extravasation of cytotoxic drugs [6,7]. Each approach has different safety and risk profiles as well as effects on the patient's quality of life [8,9]. The rate of major complications from TIVADs including both chest and arm ports ranged from 3.5 to 19% in previous studies [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“… 71 One meta-analysis of 22 studies (4131 cases, 5272 controls) in patients with breast cancer showed that arm ports were associated with a higher VTE risk than chest ports (RR 2·23, 95% CI 1·04–4·79; p=0·041). 72 In one randomised controlled trial (399 patients), peripherally inserted central catheters were associated with a higher risk of VTE and adverse events than implanted port catheters (HR 10·2, 95% CI 2·3–44·6, p=0·0002). 73 Another prospective, non-randomised study of 423 patients treated with chemotherapy via a peripherally inserted central catheter reported substantially lower rates of upper extremity VTE when patients received prophylaxis with rivaroxaban (10 mg daily; 3·76%) or enoxaparin (40 mg daily; 3·03%), compared with no prophylaxis (12·4%).…”
Section: Vte Prophylaxis In Patients With Cancermentioning
confidence: 99%